Thermal properties of lattice structures by laser powder bed fusion for aerospace systems - SÉLO, Richard Roger Joachim (2022)
In the aerospace industry, thermal management concerns numerous components but is bounded to the limitations of traditional manufacturing processes which results in inefficient and inadequately large equipment. Consequently, a change in how heat exchangers are manufactured and designed is needed. Additive manufacturing (AM) techniques such as laser powder bed fusion (LPBF) are capable of alleviating conventional design drawbacks. Among new complex structures, triply periodic minimal surface (TPMS) lattice structures are of particular interest with their high surface area to volume ratios that are ideal to increase surface-based interactions such as heat transfer. However, the adoption of LPBF for thermal applications is impeded by the lack of available material for LPBF and insufficient knowledge on how AM material thermal properties are affected by the LPBF process and of the thermal properties of lattice structures. The first part of this thesis focused on the characterisation of the thermal conductivity of materials and lattice structures manufactured by LPBF using an in-house developed testing apparatus based on the guarded comparative longitudinal heat flow technique. AlSi10Mg is the most applied aluminium alloy in LPBF, however, there is an incomplete body of knowledge surrounding its thermal conductivity. In this thesis, AlSi10Mg specimens were manufactured by LPBF and tested to characterise the effect of the unique LPBF microstructure and heat treatments on the thermal conductivity. In addition, the effect of lattice parameters on their apparent thermal conductivity was investigated by manufacturing and testing lattice structures made by LPBF in several alloys of interest for aerospace (Ti6Al4V, AlSi10Mg, and Hastelloy-X). Models were proposed to predict the thermal conductivity of lattices and specimens with tailored conductivity were manufactured.